2010
DOI: 10.1093/aobpla/plq021
|View full text |Cite
|
Sign up to set email alerts
|

The invasive ‘mothcatcher’ (Araujia sericifera Brot.; Asclepiadoideae) co-opts native honeybees as its primary pollinator in South Africa

Abstract: Araujia sericifera is a South American milkweed which is an invasive/exotic species in South Africa. This species relies on pollinators for sexual reproduction and we show it has co-opted native South African honeybees as primary pollinators in its adopted country. Moths also visit the flowers of this species, but contribute little to its relatively high pollination success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 53 publications
0
11
0
1
Order By: Relevance
“…An important future value of the Pollinators of Apocynaceae Database will be to assess a number of conservation issues. These include the extent to which introduced honey-bees ( Apis mellifera ) and other pollinators are affecting plant reproduction (and potentially selection on floral traits) as well as the ability of introduced, invasive Apocynaceae to co-opt native pollinators, for example the South American Araujia sericifera that uses honey-bees as its pollinator in South Africa (Coombs and Peter, 2010). Plant-pollinator interactions–pollinator interactions within the family present different degrees of specialization at ecological, functional or phenotypic levels ( sensu Ollerton et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…An important future value of the Pollinators of Apocynaceae Database will be to assess a number of conservation issues. These include the extent to which introduced honey-bees ( Apis mellifera ) and other pollinators are affecting plant reproduction (and potentially selection on floral traits) as well as the ability of introduced, invasive Apocynaceae to co-opt native pollinators, for example the South American Araujia sericifera that uses honey-bees as its pollinator in South Africa (Coombs and Peter, 2010). Plant-pollinator interactions–pollinator interactions within the family present different degrees of specialization at ecological, functional or phenotypic levels ( sensu Ollerton et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Rates of PTE and other measures of visitation such as pollinarium removal and pollinium deposition in Eulophia are variable both within and between species (Table ), probably as a consequence of stochastic fluctuations in foraging pollinator populations and the changes in abundance of surrounding rewarding species. PTE has rarely been tracked through the flowering period, but, where this has been done, there is variation between sample dates in rewarding species (Peter & Johnson, ; Coombs & Peter, ; Coombs et al ., ). Coombs, Peter & Johnson (), however, showed that PTE was independent of population size in a rewarding asclepiad.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other specialised species such as the Moth Catcher (Araujia sericifera), which, as its common name suggests, is moth pollinated, is largely visited by native honeybees, Apis mellifera, in South Africa. South African honeybees have learnt to access the nectar of the large moth catcher flowers (Coombs and Peter 2010). Despite the expectation that highly specialised mutualistic interactions may hamper establishment success (i.e.…”
Section: Pollinationmentioning
confidence: 99%